ПРЕВЕНТИВНА ДІЯЛЬНІСТЬ ЯК ФАКТОР ПОПЕРЕДЖЕННЯ ДЕВІАНТНОЇ ПОВЕДІНКИ ПІДЛІТКІВ (Педагогіка вищої та середньої школи, 2006)
In clause is considered questions prévention of activity as factor of the prévention déviation of behaviour of the teenagers, and also basis ofpreventive maintenance déviation of behaviour.